Comparison of Nodule Induction in Legume and Actinorhizal Symbioses: The Induction of Actinorhizal Nodules Does Not Involve ENOD40 - Carole Santi; Uritza von Groll; Ana Ribeiro; Maurizio Chiurazzi; Florence Auguy; Didier Bogusz; Claudine Franche; Katharina Pawlowski (Molecular Plant-Microbe Interactions, 2003)
Two types of root nodule symbioses are known for higher plants, legume and actinorhizal symbioses. In legume symbioses, bacterial signal factors induce the expression of ENOD40 genes. We isolated an ENOD40 promoter from an actinorhizal plant, Casuarina glauca, and compared its expression pattern in a legume (Lotus japonicus) and an actinorhizal plant (Allocasuarina verticillata) with that of an ENOD40 promoter from the legume soybean (GmENOD402). In the actinorhizal Allocasuarina sp., CgENOD40-GUS and GmENOD40-2-GUS showed similar expression patterns in both vegetative and symbiotic development, and neither promoter was active during nodule induction. The nonsymbiotic expression pattern of CgENOD40-GUS in the legume genus Lotus resembled the nonsymbiotic expression patterns of legume ENOD40 genes however, in contrast to GmENOD40-2-GUS, CgENOD40-GUS was not active during nodule induction. The fact that only legume, not actinorhizal, ENOD40 genes are induced during legume nodule induction can be linked to the phloem unloading mechanisms established in the zones of nodule induction in the roots of both types of host plants.